2018
DOI: 10.3390/nu10091175
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D Deficiency and Single Nucleotide Polymorphisms in the Vitamin D Receptor and GC Genes and Analysis of Their Distribution in Mexican Postmenopausal Women

Abstract: Genome-wide association studies in people with European ancestry suggest that polymorphisms in genes involved in vitamin D (VD) metabolism have an effect on serum concentrations of 25-hydroxyvitamin D. However, nothing is known about these polymorphisms in populations with Amerindian ancestry. Our aim was to evaluate the association between genetic variants on the vitamin D receptor (VDR) and the vitamin D binding protein (GC) genes, involved in the VD pathway, and VD deficiency in 689 unrelated Mexican postme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…On the other hand, experimental evidence has shown that some of these SNPs can influence VDBP serum levels [44,45]. Based on this, altered serum VDPB levels observed in postmenopausal women with low BMD could be influenced by these polymorphisms [46]. Additional studies are needed to evaluate the association between variants in the GC gene, serum VDBP levels, and BMD variation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, experimental evidence has shown that some of these SNPs can influence VDBP serum levels [44,45]. Based on this, altered serum VDPB levels observed in postmenopausal women with low BMD could be influenced by these polymorphisms [46]. Additional studies are needed to evaluate the association between variants in the GC gene, serum VDBP levels, and BMD variation.…”
Section: Discussionmentioning
confidence: 99%
“…Some polymorphism associated with biomarkers of inflammation, as well as those for the VD pathway, may better reflect the risk rather than serum baseline levels, since the prevalence of these polymorphs may vary across different ethnicities and populations [51]. The polymorphism associated with VDR in the Mexican population is higher in the southern region of Mexico (30%), being present in the 29% of Mayan ethnic population [52]. This risk profile may explain, that even in normal 1,25(OH2)D3 and 25(OH)D serum concentration, VD is not properly used by the cell to execute their multiple action.…”
Section: Discussionmentioning
confidence: 99%
“…When selecting SNPs (single-nucleotide polymorphisms), we aimed at choosing the ones previously reported to be associated with vitamin D-related traits in addition to a few SNPs we wanted to explore [5]. These SNPs were selected from genes associated with vitamin D and included cytochrome P450 family 2, R (CYP2R1) [5,[22][23][24][25][26][27], cytochrome P450 family 24 subfamily A member 1 (CYP24A1) [22,[27][28][29][30][31], the 1-alpha-hydroxylase (CYP27B1) [32][33][34][35], the 7-dehydrocholesterol reductase/NAD synthetase 1 (DHCR7/NADSYN1) [26,36], the vitamin D receptor (VDR) [37,38], and the vitamin D-binding protein GC (group-specific component) [20][21][22]26,28,39,40].…”
Section: Introductionmentioning
confidence: 99%